Different Responses to Pulmonary Rehabilitation in COPD Patients with Different Work Efficiencies - Jao LY; Hsieh PC; Wu YK; Yang MC; Wu CW; Lee C; Tzeng IS; Lan CC (International Journal of COPD, 2022)
Lun-Yu Jao,1,2 Po-Chun Hsieh,3 Yao-Kuang Wu,1,2 Mei-Chen Yang,1,2 Chih-Wei Wu,1,2 Chung Lee,1,2 I-Shiang Tzeng,4 Chou-Chin Lan1,2 1Division of Pulmonary Medicine, Department of Internal Medicine, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, New Taipei City, Taiwan; 2School of Medicine, Tzu-Chi University, Hualien, Taiwan; 3Department of Chinese Medicine, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation; School of Post-Baccalaureate Chinese Medicine, Tzu Chi University, Hualien, Taiwan; 4Department of Research, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, New Taipei City, TaiwanCorrespondence: Chou-Chin Lan, Division of Pulmonary Medicine, Department of Internal Medicine, Taipei Tzu Chi Hospital, Buddhist Tzu Chi Medical Foundation, 289, Jianguo Road, Xindian District, New Taipei City, Taiwan, 23142, Tel +886-2-6628-9779 ext. 2259, Fax +886-2-6628-9009, Email bluescopy@yahoo.com.twBackground: Chronic obstructive pulmonary disease (COPD) often involves the cardiopulmonary dysfunction that deteriorates health-related quality of life (HRQL) and exercise capacity. Work efficiency (WE) indicates the efficiency of overall oxygen consumption (VO2) during exercise. This study investigated whether different WEs have different effects on pulmonary rehabilitation (PR).Methods: Forty-five patients with stable COPD were scheduled for PR. The PR programs consisted of twice-weekly sessions for three months. These patients were comprehensively evaluated by cardiopulmonary exercise testing and COPD assessment test (CAT) before and after PR. We compared these parameters between patients with a normal versus poor WE.Results: Twenty-one patients had a normal WE and twenty-four patients had a poor WE (< 8.6 mL/min/watt). Patients with a poor WE had earlier anaerobic metabolism, a poorer oxygen pulse, lower exercise capacity, more exertional dyspnea, and a poorer HRQL than those with a normal WE. PR improved exercise capacity, HRQL, anaerobic threshold, exertional dyspnea and leg fatigue in patients with either normal or poor WE. However, significant improvement of WE, oxygen pulse, respiratory frequency (Rf) during exercise, chest tightness, activity and sleepiness by CAT were noted only in patients with a poor WE. Among the patients with a poor WE, 29% patients had WE returned to normal after PR.Conclusion: Patients with different WE had different responses to PR. PR improved exercise capacity and HRQL regardless of a normal or poor WE. However, WE, oxygen pulse, Rf during exercise, chest tightness, activity and sleepiness were only improved in patients with a poor WE.Keywords: chronic obstructive pulmonary disease, exercise intolerance, pulmonary rehabilitation, work efficiency